Wireless Sensor Networks - Jusic, Nisvet; Rathinavelu, Thilak (My University, 2011)
The past decade has seen a lot of research in the area of Wireless Sensor Networks. The fruits of this research was a large number of proprietary network technologies, the most successful of these being ZigBee. However as the number of technologies have grown, so had the need for standardization. Added to this was the requirement of supporting large scale networks, most of the existing technologies did not scale well with size. The result was the IETF 6LoWPAN working group. Their standards allow IPv6 to be operated on low-power networks, IPv6 being both a proven standard and reliable in large scale networking. A simple but complete network, where nodes deliver data to a central server, will be implemented and examined by this thesis, using Contiki. Developed by SICS, Contiki is one of the leading operating systems designed for low-power wireless devices. It carries SICSlowpan as its own implementation of the 6LoWPAN standard. Contiki proved to be a very advanced and capable operating system. Developing in Contiki is significantly simplified by Cooja. Cooja is a network simulator where code can be tested before it is deployed to the target hardware, on which it is often much harder to debug. Another notable advantage is the programming language, code for Contiki is written in standard C. Some of the comparable operating system require code to be written in a custom dialect or language. Finally it is presently the only operating system supporting the TCP protocol, which is required by some implementations in this thesis.
Keywords: Hållbar utveckling; Informations- och kommunikationsteknik; Elektronik; Sustainable Development; Information & Communication Technology; Electronics